Local Therapy Can Enhance the Prognosis of Certain Patients with Pathologically Diagnosed Neuroendocrine Prostate Carcinoma - Shoichi Kimura; Naoki Terada; Shinnya Soumiya; Takayuki Goto; Hiromitsu Negoro; Shoichiro Mukai; Osamu Ogawa; Shusuke Akamatsu; Takashi Kobayashi; Atsuro Sawada; Toshiyuki Kamoto (Life)
Neuroendocrine prostate cancer (NEPC) has a poor prognosis. We performed a retrospective analysis of the factors contributing to survival in patients with histologically diagnosed NEPC. Patients pathologically diagnosed with NEPC between 2007 and 2018 were retrospectively analyzed. Overall survival (OS) from the time of the initial prostate cancer diagnosis was evaluated using the Kaplan–Meier method. Cox proportional hazards analyses were performed to evaluate the association of OS with variables including the presence of metastasis, receipt of local therapy, and disease classification (primary NEPC [p-NEPC] or treatment-related NEPC [t-NEPC]). Among 32 patients (p-NEPC, 22; t-NEPC, 10), distant metastases were identified in 25 (78%) patients, and local therapies including radical prostatectomy and local radiotherapy were provided to 21 (66%) patients. In the univariate Cox proportional hazard analyses, patients who received local therapy had a significantly lower risk of death than those who did not receive local therapy (hazard ratio = 0.284, 95% confidence interval = 0.109–0.738, p = 0.01). OS was significantly longer for patients receiving local therapy than for those who did not receive local therapy (36 months vs. 13 months, p = 0.0058). Our findings suggest the potential benefit of local therapy in the treatment of NEPC.